High-efficiency and integrable DNA arithmetic and logic system based on strand displacement synthesis - Haomiao Su (Nature Portfolio, 2019)
Current DNA computational systems are constrained by integration efficiency, device structures and limited functions. Here the authors design a DNA arithmetic logic unit that uses polymerase-mediated strand displacement.